Acordos de cooperação internacional para o intercâmbio de informações fiscais e o sigilo bancário - LOBATO, Rodrigo Costa (Universidade Federal do Pará, 2019)
This study examines the constitutional foundation that legitimizes the incorporation of international agreements for tax information exchange in the Brazilian legal system and those implications for privacy and banking rights and fiscal secrecy. In the first chapter, will be analyzed the recognition of the fundamental duty to pay taxes, demonstrating that tax collection is the main source of funds for the State to finance the realization of the fundamental rights protected by the Federal Constitution. And demonstrates that the non-payment of taxes per part of society distorts the principles of tax capacity and isonomy, preventing tax justice from being achieved. In the second chapter, a brief analysis is made of the conduct and strategies adopted by taxpayers to evade paying taxes, as well as the countries where they seek refuge to practice such practices. In the third chapter, it is proposed to examine three instruments of international cooperation that Brazil adopted as an attempt to combat such practices, the Convention on Mutual Administrative Assistance in Tax Matters, the Foreign Account Tax Compliance Act (FATCA) and the BEPS Project. In a sequence, the form of internalization of international agreements and treaties in the Brazilian legal system is studied. The fourth chapter is intended to analyze the conceptions about banking and fiscal secrecy in Brazil, especially after the introduction of Complementary Law n. 105/2001 in the legal system, demonstrating the understanding of the Federal Supreme Court on its constitutionality of the norm. At the end, it is examined the possibility of relativizing the constitutional protection conferred on the right to privacy and banking secrecy, allowing direct access by the Tax Administration to the taxpayers' financial data and the international exchange of this information, and what constitutional basis for it.